Factors affecting mortality and resource use for hospitalized patients with cirrhosis: A population-based study. Issue 32 (August 2017) - Charatcharoenwitthaya, Phunchai; Soonthornworasiri, Ngamphol; Karaketklang, Khemajira; Poovorawan, Kittiyod; Pan-ngum, Wirichada; Chotiyaputta, Watcharasak; Tanwandee, Tawesak; Phaosawasdi, Kamthorn
Abstract : Abstract: Hospitalizations for advanced liver disease are costly and associated with significant mortality. This population-based study aimed to evaluate factors associated with in-hospital mortality and resource use for the management of hospitalized patients with cirrhosis. Mortality records and resource utilization for 52, 027 patients hospitalized with cirrhosis and/or complications of portal hypertension (ascites, hepatic encephalopathy, variceal bleeding, spontaneous bacterial peritonitis, or hepatorenal syndrome) were extracted from a nationally representative sample of Thai inpatients covered by Universal Coverage Scheme during 2009 to 2013. The rate of dying in the hospital increased steadily by 12% from 9.6% in 2009 to 10.8% in 2013 ( P < .001). Complications of portal hypertension were independently associated with increased in-hospital mortality except for ascites. The highest independent risk for hospital death was seen with hepatorenal syndrome (odds ratio [OR], 5.04; 95% confidence interval [CI], 4.38–5.79). Mortality rate remained high in patients with infection, particularly septicemia (OR, 4.26; 95% CI, 4.0–4.54) and pneumonia (OR, 2.44; 95% CI, 2.18–2.73). Receiving upper endoscopy (OR, 0.29; 95% CI, 0.27–0.32) and paracentesis (OR, 0.93; 95% CI, 0.87–1.00) were associated with improved patient survival. The inflation-adjusted national annual costs ( P = .06) and total hospital days ( P = .07) for cirrhosis showed a trend toward increasing during the 5-year period. Renal dysfunction, infection, and sequelae of portal hypertension except for ascites were independently associated with increased resource utilization. Renal dysfunction, infection, and portal hypertension-related complications are the main factors affecting in-hospital mortality and resource utilization for hospitalized patients with cirrhosis. The early intervention for modifiable factors is an important step toward improving hospital outcomes.